Complete genomes for hepatitis C virus subtypes 6f, 6i, 6j and 6m: Viral genetic diversity among Thai blood donors and infected spouses - Ling Lu (2018)
In this study, the first complete genome sequences for hepatitis C virus (HCV) subtypes 6f, 6i, 6j and 6m, obtained from infected blood donors in Chiang Mai, Thailand, are reported. Pairwise genome-wide nucleotide similarities between some of these isolates were higher than the 75-80 % value used previously to define different HCV subtypes. To investigate further, the entire genomes of four prototype isolates, Th602 (6i), Th553 (6j), B4/92 (6m) and D86/93 (6n), were sequenced. Pairwise comparison of these sequences gave a similar range of nucleotide similarities, thereby providing new information for HCV subtype classification. In order to study the hypothesis of interspousal HCV transmission, four additional complete HCV genome sequences were obtained from two infected Thai blood donors and their spouses, C-0044 and C-0046 (6f), and C-0192 and C-0185 (6m). Pairwise comparison of the sequences revealed that C-0044 and C-0046 share a nucleotide similarity of 98.1 %, whilst C-0185 and C-0192 have a similarity of 97.8 %. Several other studies of partial HCV sequences of different genomic regions from HCV-infected couples have shown nucleotide similarities ranging from 96.3 to 100 %. The similarities of the complete genome sequences from the two couples in the current study are consistent with HCV transmission between spouses. © 2007 SGM.